THE INFLUENCE OF SOCIAL MEDIA MARKETING AND BRAND IMAGE TO PURCHASE INTENTION THROUGH BOYCOTT PARTICIPATION AS MODERATION VARIABLE ON ROSE ALL DAY COSMETICS’s BRAND - Clarisa Salsabila; Putu Nina Madiawati; Rd. Nurafni Rubiyanti (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study examines the influence of social media marketing and brand image on purchase intention, with consumer boycott participation incorporated as a moderating variable, using Rosé All Day Cosmetics as the empirical context. Grounded in the Stimulus–Organism–Response (S-O-R) framework, a quantitative approach was employed by collecting survey data from 385 consumers in Jabodetabek and Bandung City areas, which were analyzed using PLS-SEM. The results reveal that both social media marketing and brand image have positive and significant effects on purchase intention. However, boycott participation does not moderate the relationship between social media marketing and purchase intention, while it exerts a significant negative moderating effect on the relationship between brand image and purchase intention. These findings suggest that although digital marketing and brand image remain key drivers of consumer purchase intention, moral and social considerations reflected in boycott participation can weaken the effectiveness of brand image in influencing consumer decisions. This study contributes to the literature by highlighting the contextual role of consumer boycotting in shaping marketing effectiveness within the digital beauty industry in emerging markets.